+0  
 
0
34
1
avatar

Rewrite the equation by completing the square 2x^2-3x-5=0

 Apr 18, 2020
 #1
avatar+23553 
+1

Leading coefficient needs to be  1    so filter out 2

2  (x^2 -3/2 x )     = 5     divied both sides by 2

*x^2 - 3/2 x    = 5/2

    Now take 1/2 of the x coeeficient   3/4     square it    and add it to the  equation.....both sides

    (x^2 -3/2 x + 9/16 )      = 5/2 + 9/16

(x- 3/4)^2   =  49/16       or   (x-3/4)^2 - 49/16 = 0 

 

     Now you can SOLVE it  (though Q did not ask this)    take the sqrt of both sides

 

x-3/4  = +- 7/4

x = -1   and  10/4

 Apr 18, 2020
edited by ElectricPavlov  Apr 18, 2020

34 Online Users

avatar
avatar
avatar
avatar